{-# LANGUAGE GADTs #-} module Parsers ( P , symbol , pfail , (+++) , Semantics , parse ) where -- | Naive deep embedding: each operation is implemented as a -- constructor. type P s a = Parser1 s a symbol :: P s s symbol = Symbol pfail :: P s a pfail = Fail (+++) :: P s a -> P s a -> P s a (+++) = (:+++) instance Monad (Parser1 s) where return = Return (>>=) = (:>>=) data Parser1 s a where Symbol :: Parser1 s s Fail :: Parser1 s a (:+++) :: Parser1 s a -> Parser1 s a -> Parser1 s a Return :: a -> Parser1 s a (:>>=) :: Parser1 s a -> (a -> Parser1 s b) -> Parser1 s b -- Final semantics to expose: type Semantics s a = [s] -> [(a,[s])] -- | Reference implementation/Semantics. (It's easy to see that it's what we -- want, but inefficient) run :: Parser1 s a -> Semantics s a run Symbol (c : s) = [(c, s)] run Symbol [] = [] run Fail _ = [] run (p :+++ q) s = run p s ++ run q s run (Return x) s = [(x, s)] run (p :>>= f) s = [(y, s'') | (x, s') <- run p s , (y, s'') <- run (f x) s'] {- Using this reference semantics we can prove (exercise) a number of useful laws about parsers. We will use these laws later to derive an efficient implementation of the library. Notation: [| p |] = run p For two parsers p and q we define p == q iff ∀ s. [| p |] s == [| q |] s, up to the order of elements in the result (list is interpreted as a multiset). Monad Laws L1. return x >>= f == f x L2. p >>= return == p L3. (p >>= f) >>= g == p >>= (\x -> f x >>= g) More laws about >>=, (+++) and fail L4. fail >>= f == fail L5. (p +++ q) >>= f == (p >>= f) +++ (q >>= f) Laws about (+++) and fail L6. fail +++ q == q L7. p +++ fail == p Laws about (+++) L8. (p +++ q) +++ r == p +++ (q +++ r) L9. p +++ q == q +++ p -- multisets are important here! Laws about >>=, (+++) and symbol L10. (symbol >>= f) +++ (symbol >>= g) == symbol >>= (\c -> f c +++ g c) Here is the proof of L10 for the case of a non-empty input string: [| (symbol >>= f) +++ (symbol >>= g) |] (c:s) == { semantics of (+++) } [| symbol >>= f |] (c:s) ++ [| symbol >>= g |] (c:s) == { semantics of >>= and symbol } [| f c |] s ++ [| g c |] s == { semantics of (+++) } [| f c +++ g c |] s == { semantics of symbol and >>= } [| symbol >>= (\x -> f x +++ g x) |] (c:s) Exercise: prove or test the laws -} {- The reference semantics is useful for reasoning, but inefficient. There are three sources of inefficiency that we can identify: 1. The list comprehension builds a lot of intermediate lists which might be costly. 2. List append (++) is linear in its first argument which means that left nested applications of (+++) get a quadratic behaviour. 3. (+++) is treated in a depth first way, first computing the results of the left parser, then computing the results of the second parser. This leads to a space leak since we have to hang on to the input string to feed to the second parser, while traversing the string with the first parser. -} -- To solve them we'll invent clever intermediate representations. -- Can we linearize sequencing (>>=)? (Would help with 1.) data Parser2 s a where SymbolBind2 :: (s -> Parser2 s a) -> (Parser2 s a) -- SymbolBind f ≜ Symbol >>= f Return2 :: a -> Parser2 s a (::+++) :: Parser2 s a -> Parser2 s a -> Parser2 s a Fail2 :: Parser2 s a runParser2 :: Parser2 s a -> Semantics s a runParser2 (SymbolBind2 y) [] = [] runParser2 (SymbolBind2 y) (x : xs) = runParser2 (y x) xs -- ~= run (Symbol >>= f) (x:xs) runParser2 (Return2 y) l = [ (y , l) ] runParser2 (y ::+++ y') l = runParser2 y l ++ runParser2 y' l runParser2 Fail2 l = [] -- But it turns out that we can translate Parser1 into Parser2! p12 :: Parser1 s a -> Parser2 s a p12 Symbol = SymbolBind2 Return2 -- L1 p12 Fail = Fail2 p12 (y :+++ q) = p12 y ::+++ p12 q p12 (Return y) = Return2 y p12 (Symbol :>>= q) = SymbolBind2 (\c -> p12 (q c)) -- def of SymbolBind p12 (Fail :>>= q) = Fail2 -- Parser law. L4. p12 ((y :+++ q) :>>= y0) = p12 (y :>>= y0) ::+++ p12 (q :>>= y0) -- Parser law. L5 p12 (Return y :>>= q) = p12 (q y) -- monad law, L1 p12 ((p :>>= k') :>>= k) = p12 (p :>>= (\x -> k' x :>>= k)) -- monad law, L3 -- Can we linearize choice as well (+++)? data Parser3 s a where SymbolBind3 :: (s -> Parser3 s a) -> Parser3 s a ReturnChoice3 :: a -> Parser3 s a -> Parser3 s a -- ReturnChoice x p ≜ Return x +++ p Fail3 :: Parser3 s a runParser3 :: Parser3 s a -> Semantics s a runParser3 (SymbolBind3 y) [] = [] runParser3 (SymbolBind3 y) (x : xs) = runParser3 (y x) xs runParser3 (ReturnChoice3 y q) l = (y , l) : runParser3 q l -- ~= run (Return x +++ p) runParser3 Fail3 l = [] -- But it turns out that we can translate 2 into 3! p23 :: Parser2 s a -> Parser3 s a p23 (SymbolBind2 y) = SymbolBind3 (\s -> p23 (y s)) p23 (Return2 y) = ReturnChoice3 y Fail3 -- def. of returnchoice p23 (p ::+++ q) = best (p23 p) (p23 q) p23 Fail2 = Fail3 best :: Parser3 s a -> Parser3 s a -> Parser3 s a best (SymbolBind3 y) (SymbolBind3 q) = SymbolBind3 (\s -> best (y s) (q s)) -- L10 best p (ReturnChoice3 x q) = ReturnChoice3 x (best p q) -- L8 (+++ commut) best (ReturnChoice3 x q) p = ReturnChoice3 x (best p q) -- L9 (+++ assoc) best p Fail3 = p -- L6 best Fail3 q = q -- L7 -- | Efficient implementation for general syntax: parse :: P s a -> Semantics s a parse = runParser3 . p23 . p12 -- we could show formally: -- (x , s) ∈ run p ss <=> (x , s) ∈ runParser2 (1to2 p) ss -- (x , s) ∈ runParser2 p ss <=> (x , s) ∈ runParser3 (2to3 p) ss -- and therefore: -- (x , s) ∈ run p ss <-> (x , s) ∈ parse p ss -- Exercise: prove or test {---------------------- NOTES: * L4 to L10 are "parser laws", expected to hold of any well-behaved parser. -}